Analysis of the perception of urban mobility by users in the city of Manaus (Research, Society and Development, 2022)
The unbridled growth of urban spaces brings a series of noticeable problems in both the urban and social landscapes being, disordered growth in peripheral areas, imbalance in income distribution socio-spatial segregation, among others. The objective of this work was to analyze the perception of urban mobility of users of public and private transport in the city of Manaus. Questionnaire with objective Google forms were applied to 182 users of private transport (cars and motorcycle) and collective passenger, aiming to analyse their perceptions about urban mobility in the capital of Amazonas. Users stated that Manauaras streets do not offer good traffic conditions and drivers are not prepared to deal with reality, drivers pointed out that more than 80% of accidents are caused by recklessness, although road conditions contribute and even though congestion on the main streets of the city is due to the large number of vehicles. They believe that increasing bike lanes as an alternative to reducing the number of motor vehicles would not be enough to achieve this goal, but investment in quality public transport, driver education, etc, would contribute to more sustainable urban mobility. It is a fact that there are no magical solutions, but the beginning by the education of the manauara driver for respect for signage, for example, it would be a significant and for reducing congestion, as well as reducing accidents and manaura’s stress in driving through the city roads and consequently the environmental problem formed by the whole.